Nucleation process of an M2 earthquake in a deep gold mine in South Africa inferred from on‐fault foreshock activity. Issue 8 (6th August 2015) - Yabe, Yasuo; Nakatani, Masao; Naoi, Makoto; Philipp, Joachim; Janssen, Christoph; Watanabe, Takayoshi; Katsura, Taishi; Kawakata, Hironori; Georg, Dresen; Ogasawara, Hiroshi
Abstract Using a network of sensitive high‐frequency acoustic emission sensors, we observed foreshock activity of an Mw 2.2 earthquake (main shock) in a deep gold mine in South Africa. Foreshock activity, which selectively occurred on a part of the rupture plane of the forthcoming main shock, lasted for at least 6 months until the main shock. Rock samples recovered from the main shock source region showed evidence of ancient hydrothermal alteration on the main shock rupture plane, suggesting that the foreshock activity occurred on a preexisting weakness. The foreshocks during 3 months before the main shock were concentrated in three clusters (F1–F3), which we interpret as representing localized preslip at multiple sites. While the location of mining area, the source of stress perturbations, changed with time, the locations of foreshock clusters did not change, suggesting that the preslip patches were controlled by strength heterogeneity rather than stress distribution. Activity over the entire foreshock area was generally constant, but the largest cluster (F2) showed accelerated activity starting at least 7 days before the main shock, while mining stress did not increase in this period. The main shock initiated at a point close to F1, away from F2. All the six foreshocks during the final 41 h occurred in F1 and F2 and in‐between. These suggest that in the last stage of the preparation process of the main shock, preslip patches interacted with each other through the stress concentration ahead of the expanding preslip patch (F2), which should be the only driving force of the preparation process under the constant external load.